How Do Consumers Understand Food Processing? A Study on the Brazilian Population - Jordanna Santos Monteiro; Eduardo Yoshio Nakano; Renata Puppin Zandonadi; Raquel Braz Assunção Botelho; Wilma Maria Coelho Araujo (Foods, 2022)
Food guides are official documents that guide consumers’ food choices. They inform the qualitative classification of food groups and messages on how to adopt a healthy diet. The classifications and nomenclatures adopted in these documents vary according to cultural, nutritional, and scientific criteria. This study aimed to evaluate the understanding of Brazilian consumers regarding food classification according to the Food Guide for the Brazilian Population (FGBP) concepts. An instrument was constructed to assess consumer understanding. It was named “Understanding of the Level of Processing of Food” (ULPF) and validated according to the concepts of constructs presented by psychometrics such as the Delphi methodology. The instrument was composed of 36 items approved by experts (concordance > 80% and with good internal consistency). A total of 2333 Brazilians from all regions participated in the study. The results suggest that food classification according to the level of processing was difficult for participants to understand. About 85% of them did not understand or did not know the definitions and classification of food and preparations according to food and science technology (FST) and the FGBP. More than 50% of the participants believed that it was easier to classify food according to food groups.